The origins, processes and emerging outcomes of neighbourhood redevelopment in Gaziosmanpaşa, Istanbul - Gökşin, Zeynep Ayşe; Erkan Yazıcı, Yazıcı; TÖRE, EVRİM ÖZKAN (Athens Instittute for Education and Research, 2016)
Large scale neighbourhood redevelopment programmes are emerging in Turkish cities which are implementing a national policy commitment to the demolition and replacement of 6 million earthquake vulnerable homes, over a period of 20 years. This phenomenon is analysed with particular references to the Istanbul Municipal District of Gaziosmanpaşa. The homes affected are mainly in poor, illegally developed, gecekondu neighbourhoods which are the legacy of the explosive post-war urbanisation. In the aftermath of the devastating 1999 Marmara earthquake, the Turkish authorities initiated the development of the legal and institutional framework for neighbourhood redevelopment which culminated in the Urban Regeneration Law of 2012. This was a controversial process which included several projects that were heavily criticised for causing displacement, dispersal and forced evictions. The case study of the on-going redevelopment of the Sarıgöl neighbourhood identifies the processes which continue to generate these negative outcomes and sustained opposition from residents, professional bodies and academics.
Keywords: displacement; Gaziosmanpaşa; Istanbul; neighbourhood redevelopment; participation